2018
DOI: 10.1038/s41598-018-24289-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biogeography of the gut microbiome between Jinhua and Landrace pigs

Abstract: The intestinal microbiome is critically important in shaping a variety of host physiological responses. However, it remains elusive on how gut microbiota impacts overall growth and more specifically, adipogenesis. Using the pig as an animal model, we compared the differences in bacterial community structure throughout the intestinal tract in two breeds (Landrace and Jinhua) of pigs with distinct phenotypes. The Landrace is a commercial purebred and the Jinhua is a Chinese indigenous, slow-growing breed with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
113
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 30 publications
10
113
4
Order By: Relevance
“…Fecal swab samples were used to represent swine gut microbiota. Although not ideal due to the biogeography variation of swine gut microbiota [47], fecal rectal swabs are the best samples to represent the gut microbiome for longitudinal studies to follow the same sets of animals without sacrificing the animals. Our results indicated that the peptide and high-level ZnO combination…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fecal swab samples were used to represent swine gut microbiota. Although not ideal due to the biogeography variation of swine gut microbiota [47], fecal rectal swabs are the best samples to represent the gut microbiome for longitudinal studies to follow the same sets of animals without sacrificing the animals. Our results indicated that the peptide and high-level ZnO combination…”
Section: Discussionmentioning
confidence: 99%
“…Fecal swab samples were used to represent swine gut microbiota. Although not ideal due to the biogeography variation of swine gut microbiota [47], fecal rectal swabs are the best samples to represent the gut microbiome for longitudinal studies to follow the same sets of animals without sacrificing the animals. Our results indicated that the peptide and high-level ZnO combination restored the performance parameters of the weanling piglets fed nutrient-deficient diets, particularly at the highest peptide concentration (0.5%) level, whereas peptide supplementation at each concentration with standard-level zinc failed to produce any improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the average diameter of adipocytes in low body weight chickens was much larger indicating that more synthesized fat was stored in abdominal adipose tissue in low body weight chickens. As a result, excessive fat deposition affected growth performance [45]. These results indicate that the differential fat metabolism level is the key factor leading to differences in growth performance.…”
Section: Discussionmentioning
confidence: 86%
“…At the same time, the expression of fat catabolism-related genes increased, ultimately promoting the oxidative catabolism of fatty acids, thereby providing energy for the growth and development of chickens [42][43][44]. Abdominal adipose tissue is the main organ of fat synthesis and deposition; the upregulated expression of adipocyte differentiationrelated genes can mediate excessive proliferation and differentiation of adipocytes, causing excessive deposition of fat in animal bodies [45]. In the present study, the expression of fat synthesis-and adipocyte differentiation-related genes in low body weight chickens was signi cantly higher than in high body weight chickens, increasing fat synthesis in abdominal adipose tissue.…”
Section: Discussionmentioning
confidence: 99%